The role of artistic activities in developing the soft skills required for the labor market from the perspective of faculty of education students(Field study at lattakia university) (Journal of Hama University, 2026)
The research aims to examine the role of artistic activities in developing the soft skills required for the labor market from the perspective of faculty of education students, it also seeks to identify the obstacles that hinder the implementation of these activities, and to propose  mechanisms that can enhance their effectiveness. as well as to explore whether there are differences between the averages of students' scores in role of artistic activities in developing the soft skills of according to the variable (the work) .To achieve the research , The descriptive approach was used and the sample consisted to (90) students of faculty of education at lattakia university. The researcher has prepared a questionnaire  to measure the role of artistic activities in developing the soft skills. The instrument included (42) items, divided into two axes: the first axis consists of (30) items, divided into six dimensions:(communication, time management, leadership, collaboration, problem- solving, and creativity & innovation),while the second axis consists of (12) items. In addition, the questionnaire includes an open- ended question.The finding revealed that:Role of artistic activities in developing the soft skills required for the labor market from the perspective of students was rated at a high level.The main challenges hindering the effectiveness of artistic activities were identified as:( negative societal attitudes toward artistic activities, Limited integration of digital technologies, and an Excessive focus on theoretical aspects at the expense of practical application)The key suggestions for improving role of artistic activities are (Increasing the number of practical training hours allocated to academic courses, and Organizing training workshops for instructors to strengthen their capacity for continuous implementation of artistic activities)There are no statistically significant differences between the averages of the sample members’ answers about role of artistic activities in developing the soft skills depending on the variable of work. Key words: Artistic Activities- Soft Skills- Faculty of Education students
Keywords: Key words: Artistic Activities- Soft Skills- Faculty of Education students.